Effects of Arbuscular Mycorrhiza-Enriched Bio-compost and Organic Fertilizer on Reducing Heavy Metal Absorption in Shallots - Muhammad Akhsan Akib; Sarjiya Antonius; Tutik Kuswinanti; Syatrawati Syatrawati; Tirta Kumala Dewi; Entis Sutisna (PLANTA TROPIKA, 2025)
Shallots have physiological and pharmacological effects on the human body and have been cultivated intensively using bio-compost, which might be contaminated with heavy metals. The main objective of this study is to enrich arbuscular mycorrhizal fungi (AMF) in bio-compost and add biological organic fertilizer (BOF) to reduce the absorption of heavy metals in shallot bulbs. The study was conducted in Enrekang District, South Sulawesi, where the components of heavy metal content in plant organs and the level of infection of AMF in plant roots were observed. The study was a filed research arranged in a Randomized Block Design with five treatments, including shallots cultivation method by indigenous farmers/control(B0) and using various doses of bio-compost enriched with AM fungi of 100kg plot-1(B1); 200kg plot-1(B2); 100kg plot-1+BOF(B3); and 200kg plot-1+BOF). The results showed that bio-compost enriched with AMF at a dose of 200 kg plot-1 and 100kg plot-1+BOF could increase Cr, Cu, and Pb accumulation in roots and leaf, as well as reduce metal accumulation in shallot bulbs, with the level of AMF infection classified as very high. The novelty of this study is that organic fertilizer enriched with AMF can reduce the absorption of heavy metals accumulated in shallot bulbs.